Respuesta :

Answer:

D

Step-by-step explanation:

the answer of the question above is

-3x⁵-7x³+ 18x² + 42

Answer:  Choice D

-3x^5 - 7x^3 + 18x^2 + 42

===================================================

Work Shown:

(3x^2 + 7)(6 - x^3)

y(6 - x^3) ........ let y = 3x^2+7

y*6 - y*x^3 ..... distribute

6y - x^3y

6( y ) - x^3( y )

6( 3x^2+7 ) - x^3( 3x^2+7 ) ..... plug in y = 3x^2+7

6*3x^2 + 6*7 - x^3*3x^2 - x^3*7 .... distribute twice more

18x^2 + 42 - 3x^5 - 7x^3

-3x^5 - 7x^3 + 18x^2 + 42